2009
DOI: 10.1158/0008-5472.can-09-1921
|View full text |Cite
|
Sign up to set email alerts
|

RAS Mutations Affect Tumor Necrosis Factor–Induced Apoptosis in Colon Carcinoma Cells via ERK-Modulatory Negative and Positive Feedback Circuits Along with Non-ERK Pathway Effects

Abstract: More than 40% of colon cancers have a mutation in K-RAS or N-RAS, GTPases that operate as central hubs for multiple key signaling pathways within the cell. Utilizing an isogenic panel of colon carcinoma cells with K-RAS or N-RAS variations, we observed differences in tumor necrosis factor-A (TNFA)-induced apoptosis. When the dynamics of phosphorylated ERK response to TNFA were examined, K-RAS mutant cells showed lower activation whereas N-RAS mutant cells exhibited prolonged duration. These divergent trends we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 41 publications
5
48
0
Order By: Relevance
“…AKT and ERK activation were indeed observed in K-ras mutated DLD1 cells. [25][26][27] Our data showed that Bcl-2 expression in DLD1 cells was nearly diminished by AKT or ERK inhibitor (Supplementary Figure 7b). Therefore, Bcl-2 expression in DLD1 cells may be through the activation of ERK and AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 73%
“…AKT and ERK activation were indeed observed in K-ras mutated DLD1 cells. [25][26][27] Our data showed that Bcl-2 expression in DLD1 cells was nearly diminished by AKT or ERK inhibitor (Supplementary Figure 7b). Therefore, Bcl-2 expression in DLD1 cells may be through the activation of ERK and AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 73%
“…In rat pulmonary myofibroblasts, VP induced ERK-1/2 activation and that the activation was oxidant dependent and EGFR-mediated [36]. In colon, cancer cells lines, it has been demonstrated that KRAS mutational status impacts the apoptotic response mediated by TNF-␣ and extracellular signal-related kinases (ERK) pathway activation [37]. Thus, the finding that Kras tumor mutation is correlated with increased MAPK pathway activation could be consistent with either an oxidative stress/Kras-mediated mechanism or an inflammatory microenvironment/Kras-mediated mechanism [23].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that MKP-mediated negative feedback is a major determinant of pathway activity in Ras/ERK-driven cancers (8). Increased MKP levels are detected in a variety of cancer cells with activated KRas or BRaf and are presumed to suppress ERK activity (9)(10)(11)(12). Ectopic expression of DUSP5 in lung and colon cancer cells lowers ERK activity and suppresses growth (13).…”
mentioning
confidence: 99%